A Diversity of Copepods in Gajah Mungkur in Wonogiri Regency, Central Java, Indonesia - Efri Roziaty; Afrika Arianto; Vina Listiawati (Universitas Muhammadiyah Surakarta, 2023)
GajahMungkur Reservoir is a freshwater ecosystem thatis located6kmsouthofWonogiri Regency,CentralJavaProvince. Zooplankton is the primary consumer in the food chain of aquatic ecosystems. One of the common zooplankton found in freshwater ecosystem is copepod. Copepod is sensitive organism and play an important role as bioindicatator of water quality. The aimed of this study was to investigate the copepods diversity in Gajah Mungkur Reservoir. The method applied to this study is exploration and application of purposive sampling techniques in sampling. Copepods were collected from three different station, namely Station 1 (fishing area), Station 2 (tourism area), and Station 3 (fish cage area or keramba). The abiotic parameters were found to be varied on each station. Results showed that Gajah Mungkur Reservoir has moderately diverse copepods species with the average of diversity index 1.21. There were 7 species of copepods found in Gajah Mungkur Reservoir which mostly dominated by Mesocyclops sp., especially in Station 1 (fishing area). Meanwhile Microcyclops sp. was only found in Station 3 (fish cage area or keramba), suggesting that this species has a potential as bioindicator in Gajah Mungkur Reservoir. This study suggest that changes in physicochemical parameters might influence the diversity and abundance of copepod in Gajah Mungkur Reservoir.